2020
DOI: 10.3390/w12092464
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in the Free Stream Region of Turbulent Flows through Emergent Rigid Vegetation on Rough Beds

Abstract: Most of the existing works on vegetated flows are based on experimental tests in smooth channel beds with staggered-arranged rigid/flexible vegetation stems. Actually, a riverbed is characterized by other roughness elements, i.e., sediments, which have important implications on the development of the turbulence structures, especially in the near-bed flow zone. Thus, the aim of this experimental study was to explore for the first time the turbulence anisotropy of flows through emergent rigid vegetation on rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Experimental studies of velocity profiles, like those shown in Figures 3-5, are of much interest; in some cases also the shear stress profiles are studied by means of velocity fluctuant components and Reynolds stress theory [19,[107][108][109][110][111].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of velocity profiles, like those shown in Figures 3-5, are of much interest; in some cases also the shear stress profiles are studied by means of velocity fluctuant components and Reynolds stress theory [19,[107][108][109][110][111].…”
Section: Methodsmentioning
confidence: 99%
“…The author gives, for every class of channels, the minimum, average, and maximum values of Manning n coefficient, warning that when the channel is artificial, the average values should be used in case of good maintenance only. In Tables 5 and 6 of Chow's book ( [47], p. [110][111][112][113], one can observe that the Manning coefficient is 0.018 sm −1/3 in case of the excavated channel, straight, clean, uniform cross-section with no vegetation, and 0.035 sm −1/3 in case of dense weeds. In natural streams, its values are 0.030 sm −1/3 when the cross-section is clean, and 0.045 sm −1/3 in case of weeds.…”
Section: Descriptive and Photographic Comparison Approachesmentioning
confidence: 99%
“…Moreover, the Reynolds shear stresses present very small values, practically vanishing in the region dominated by the vegetation [16,22]. Very recently, Penna et al [24,25] studied the flow field around a rigid cylinder in three different rough bed conditions with a uniform pattern of stems that are regularly aligned. Penna et al [24] analyzed the velocity, shear stress distributions, TKE and the energy spectra, showing that, in the region near the free surface, the flow is deeply affected by the stems.…”
Section: Laboratory Experiments and Methodologymentioning
confidence: 99%
“…Moving toward the bed surface, the flow is influenced by both the vegetation and bed roughness effects. Penna et al [25], using the so-called Anisotropy Invariant Maps (AIMs), investigated for the first time the turbulence anisotropy through uniform emergent rigid vegetation on rough beds. The study of the AIMs indicated that, approaching the bed surface, the combined impact of vegetation and bed roughness affects the turbulence evolution from the quasi-three-dimensional isotropy to axisymmetric anisotropy.…”
Section: Laboratory Experiments and Methodologymentioning
confidence: 99%
See 1 more Smart Citation